Cloning Journalism Practices and Violations of Journalistic Ethics (Case Study of Press Company Organizations in Bengkulu Local Media) - Imran, Tri Yulianti; Gushevinalti, Gushevinalti; Marlina, Neneng Cucu (East Asian Journal of Multidisciplinary Research, 2024)
This thesis is entitled "Clone Journalism Practices and Violations of Journalistic Ethics (Case Study of Press Company Organizations in Bengkulu Local Media)". The aim of this research is to present the practice of cloned journalism and violations of journalistic ethics in case studies of press company organizations in the local Bengkulu media. This research uses a descriptive analysis method with a qualitative approach. In the practice of cloning journalism and violations of journalistic ethics based on the code of ethics guidelines created by the Press Council and regulated in Law No. 40 of 1999. By paying attention to news elements such as news titles, leads, news content, and quotations using Galtung's gate keeper theory and Ruge (McQuail, 2010:310). The research results show that local media in Bengkulu have carried out the practice of cloning journalism on news published in their respective media. Researchers also found that the media that most often practice clone journalism are media that are members of the Benkulu press company organization, namely the Indonesian Cyber Media Union (SMSI). The practice of cloning journalism is an ethical violation committed by many elements. Starting from journalists, and editors to editor-in-chief. This practice is carried out systematically and the editors do not function in editing and editing news. The practice of cloning journalism is a violation of journalistic ethics in article 2 which states that Indonesian journalists must use professional methods in carrying out journalistic practices.